2003
DOI: 10.1016/s0969-2126(03)00073-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of Sialic Acid-Based Siglec Inhibitors and Crystallographic Analysis in Complex with Sialoadhesin

Abstract: The Siglec family of receptors mediates cell surface interactions through recognition of sialylated glycoconjugates. The crystal structure of the N-terminal immunoglobulin-like domain of the Siglec sialoadhesin (SnD1) in complex with 2,3-sialyllactose has informed the design of sialic acid analogs (sialosides) that bind Siglecs with significantly enhanced affinities and specificities. Binding assays against sialoadhesin (Sn; Siglec-1), CD22 (Siglec-2), and MAG (Siglec-4) show a 10- to 300-fold reduction in IC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 51 publications
10
117
2
1
Order By: Relevance
“…This key difference must be taken into account in the rational design of inhibitors for each ortholog of CD22. Modeling studies of Zaccai et al (50) indicated a hydrophobic pocket in CD22 adjacent to the 9-position of sialic acid, and further identified biphenyl substituents at that position, BPC and BPA, that increased the affinity of NeuAc for hCD22 and mCD22, respectively (50,56). Using a chemoenzymatic approach (33, 41), we assembled the specificity elements preferred by hCD22 and mCD22 into the sequences 9-BPC-NeuAc␣2-6Gal␤1-4GlcNAc␤-ethylamine (BPC-NeuAc-LN) and 9-BPA-NeuGc␣2-6Gal␤1-4GlcNAc␤-ethylamine (BPA-NeuGc-LN), resulting in inhibitory potencies (IC 50 values) of 1-2 M for hCD22 and mCD22, respectively ( Fig.…”
Section: Development Of High-affinity Sialoside Ligands Of Cd22mentioning
confidence: 99%
See 1 more Smart Citation
“…This key difference must be taken into account in the rational design of inhibitors for each ortholog of CD22. Modeling studies of Zaccai et al (50) indicated a hydrophobic pocket in CD22 adjacent to the 9-position of sialic acid, and further identified biphenyl substituents at that position, BPC and BPA, that increased the affinity of NeuAc for hCD22 and mCD22, respectively (50,56). Using a chemoenzymatic approach (33, 41), we assembled the specificity elements preferred by hCD22 and mCD22 into the sequences 9-BPC-NeuAc␣2-6Gal␤1-4GlcNAc␤-ethylamine (BPC-NeuAc-LN) and 9-BPA-NeuGc␣2-6Gal␤1-4GlcNAc␤-ethylamine (BPA-NeuGc-LN), resulting in inhibitory potencies (IC 50 values) of 1-2 M for hCD22 and mCD22, respectively ( Fig.…”
Section: Development Of High-affinity Sialoside Ligands Of Cd22mentioning
confidence: 99%
“…To create high-affinity probes for B cell targeting, we combined molecular features previously reported to enhance the affinity for CD22. Accordingly, 9-biphenyl substituents of sialic acid shown by Zaccai et al (50) to increase the affinity of CD22 were incorporated into the preferred sialoside ligands of human and murine CD22, and subsequently attached to a high m.w. polyacrylamide backbone to provide a highly multivalent construct.…”
mentioning
confidence: 99%
“…Sialic acids are afamily comprising of over 40 kinds of derivatives of N-acetylneuraminicacid(Neu5Ac), with structural diversity generatedbys ubstitutions at thecarbonpositions 4, 5, 7, 8 and9 [1,2],which can take part in alarge variety of biological functions including recognition phenomena [3].Asconsequence, they are usually exploited as anti-influenza drugs and substrates of detecting influenza [4,5].Inthis work, we present aderivative, namely 4,7-di-O-methyl 8,9-O-isopropylidine Neu5Ac methyl estermethylketoside. Crystalstructure and spectroscopic characterization ared escribed herein.T he unit cell of this compound contains four 4,7-di-O-methyl 8,9-O-isopropylidine Neu5Ac methyl ester methyl ketoside molecules.…”
Section: Discussionmentioning
confidence: 99%
“…All Hatoms on Catoms were generated geometrically andrefined as riding atomsw ith d(C-H) =0 .96-0.98 Å, and U iso (H) =1 .2 U eq (C) for Ca toms of CH 2 and CH groups and U iso (H) =1 .5 U eq (C) for Catoms of CH 3 groups. The hydrogen atom of the N1 atom has been added on the basis of the Q peak, the bond H-N has been constrained with 'dfix' command in ad istance of 0.82 Å, with adeviation of 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless, a 10 M concentration of disialyl T antigen was efficacious, and the toxicity of saccharides is characteristically low. Thus, testing of sialoglycans for their ability to enhance axon regeneration in nerve injury models in vivo may be feasible and provides impetus for identifying further structural refinements that may generate yet higher affinity sialoglycan inhibitors (51).…”
Section: Fig 6 Benzyl-␣-galnac Treatment Does Not Reverse Mag-mediamentioning
confidence: 99%